(untitled) (Research, Society and Development, 2021)
Objectives: To evaluate the effectiveness of mindfulness as a complementary therapy in patients with rheumatoid arthritis. Method: Protocol numbered CRD42017080108 on the PROSPERO platform. Manual searches and the Cochrane Collation assessment instrument were performed for systematic reviews in the databases CENTRAL, MEDLINE, PEDro, PsycoINFO, LILACS, Web of Science, clinical trials.gov, WHO-ICTRP and Open Gray. Randomized controlled trials were included without language restrictions or mindfulness temporality compared to placebo, psychotherapy or another equivalent strategy in patients with rheumatoid arthritis. Results: Four primary studies included (249 participants), which compared mindfulness with waiting lists, cognitive therapy and education. They presented better scores of disease activities, depressive symptoms, psychological distress, well-being, pain catastrophization, although they were classified as having a high risk of occurrence in at least one domain of the instrument used, presenting the need for robust clinical trials, proving the effectiveness of mindfulness in clinical practice. Conclusions: Beneficial effects of mindfulness in patients with rheumatoid arthritis are shown to present important results of changes in outcomes that affect the biopsychosocial dimensions in patients with. However, the evidence from the studies evaluated is of low quality, making it difficult to recommend intervention in clinical practice.